One pearl from the precious string. Series 3, Issue 3. - Hassan @ Mohamed, Nor Jana (Centre for Islamisation (CENTRIS), IIUM, 2025)
We greet you in this blessed month of Mawlid al-Rasūl - Allāhumma ṣalli ‘alā Sayyidina Muḥammad - after a month of retreat, to proceed with the third issue of series no. 3 September 2025, detailing the ‘HOW’ of IOHK according to what had been laid out by al-marḥūm Emeritus Professor Tan Sri Dr. Mohd Kamal Hassan, IIUM’s 3rd Rector. Issue 2 no. 3 briefly lays down the third methodology for Islamisation, namely “Weeding Out the Munkarāt” and “Reaffirming the Ma‘rūf”. This essentially is al-Amru bi al-Ma‘rūf wa Nahy ‘an al-Munkar aspect of IOHK, founded on Al-Furqān, the criterion of the Qur’an and Sunnah. Related to the above, we proceed with three further ways, by which IOHK can, and must be implemented.